Aortic systolic blood pressure predicts periprocedural myocardial injury after transcatheter aortic valve implantation. (14th October 2021) - Terentes-Printzios, D; Gardikioti, V; Latsios, G; Drakopoulou, M; Siasos, G; Oikonomou, E; Mpei, E; Xanthopoulou, M; Christoforatou, E; Toutouzas, K; Vavuranakis, M; Tsioufis, K; et al.
Abstract: Background/Introduction: Periprocedural myocardial injury (PPMI) is a complication of transcatheter aortic valve implantation (TAVI) associated with worse outcome. Central (aortic) systolic blood pressure (SBP) is an independent predictor of cardiovascular events. Purpose: We sought to investigate the effect of TAVI on peripheral and central hemodynamics, as well as the predictive ability of brachial and aortic SBP for PPMI. Methods: We enrolled 70 patients (mean age 79.9±8.7 years, 50% males) with severe symptomatic aortic valve stenosis (AVS) undergoing TAVI. Brachial pressures were measured with an oscillometric device and central pressures were assessed by arterial tonometry at baseline and after the procedure at discharge. PPMI was identified based on Valve Academic Research Consortium (VARC-2) criteria. Biomarkers for MI (cardiac troponin and creatinine kinase MB) were analyzed and signs and symptoms according to VARC-2 criteria were collected from clinical records. Stepwise multivariable regression analysis was performed for the prediction of PPMI. Results: According to VARC-2 definition, 38 (54%) patients had PPMI. In stepwise multivariable regression analysis, brachial SBP at baseline was not predictive of PPMI (p=0.07) after adjusting for age, sex and history of coronary artery disease. On the contrary, aortic SBP predicted PPMI even after adjustment for the abovementioned confounders (Odds ratio [OR]=1.032, 95% Confidence Interval [CI] 1.004–1.061, p=0.026). Interestingly, both SBP and aortic SBP were higher at discharge in patients with PPMI compared to patients without PPMI after adjustment (p=0.021 and p=0.006, respectively). On the contrary, the periprocedural changes of aortic SBP and SBP were not different between patients with PPMI and without PPMI. Conclusions: Aortic SBP, as assessed by tonometry, is an independent predictor stronger than brachial SBP for PPMI in AVS patients treated with TAVI. This finding suggests the possible clinical role of aortic pressures as a risk stratification tool for PPMI prior to TAVI, as well as, warrants further investigation on their role as therapeutic targets to decrease the incidence of PPMI. Funding Acknowledgement: Type of funding sources: None.